Corporate Governance and Carbon Emission Disclosure: Media Exposure as A Moderation - Awaliyah, Risalatul; Ardianingsih, Arum (Fakultas Ekonomi Universitas Garut, 2024)
The disclosure of carbon emissions is a corporate activity to provide information about environmental performance and efforts to improve the corporate image. The aim of the research is to provide empirical evidence of the moderating influence of media exposure on the relationship between corporate governance and carbon emissions disclosure. This study uses a quantitative approach. Data research was taken using the purposive sampling method. Research was conducted on energy corporations listed on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. The research used 72 research data. The analysis technique uses SEM PLS. The results of the research are that the board of directors influences carbon emissions disclosure and media exposure is able to moderate the relationship between the board of directors and carbon emissions disclosure.